![E(x)=(1 supra x-2-xsupra x^{2} -4):2 supra (x-2)(x+2) E(x)=(1 supra x-2-xsupra x^{2} -4):2 supra (x-2)(x+2)](https://tex.z-dn.net/?f=E%28x%29%3D%281+supra+x-2-xsupra+++x%5E%7B2%7D+-4%29%3A2+supra+%28x-2%29%28x%2B2%29)
va roog ajutati-ma!
Răspunsuri la întrebare
Răspuns de
0
Ex=( 1/x-2 -x/(x-2) (x+2) ) * (x-2)(x+2)/2
=(x+2-x)/(x-2)(x+2) *(x-2)(x+2)/2
=1
=(x+2-x)/(x-2)(x+2) *(x-2)(x+2)/2
=1
Alte întrebări interesante
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă